2017
DOI: 10.4186/ej.2017.21.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Dynamic Behaviour of a Biological Wastewater Treatment Plant in South East Queensland, Australia using Bio-Win Software

Abstract: Wastewater treatment is the process of removing pollutants from liquid waste using physical, chemical and biological methods by converting it into an acceptable final effluent before discharging into a water body or reuse, and to safely dispose of solids generated during the treatment process. Limited parameters in Wastewater Treatment Plant (WWTP) are usually measured due to the significant cost and time involved with them. The mathematical modelling is increasingly becoming a well-established technique among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…50 BioWin, for example, is a flexible software tool that includes multiple microbial processes presented in ASMs and anaerobic digestor models (ADMs). [51][52][53][54][55] It has been used to model the biological systems in full-scale wastewater treatment plants, [52][53][54][55] including activated sludge, 56 anaerobic digestion, 57,58 and anammox processes. 51 In some of the studies, BioWin provided a good match between the measured and predicted data (difference <10%) for both small-scale batch reactors and full-scale systems, [56][57][58] and it can perform optimization of sludge retention time and nitrogen removal under different DO and return activated sludge flows.…”
Section: Modeling Of Activated Sludge Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…50 BioWin, for example, is a flexible software tool that includes multiple microbial processes presented in ASMs and anaerobic digestor models (ADMs). [51][52][53][54][55] It has been used to model the biological systems in full-scale wastewater treatment plants, [52][53][54][55] including activated sludge, 56 anaerobic digestion, 57,58 and anammox processes. 51 In some of the studies, BioWin provided a good match between the measured and predicted data (difference <10%) for both small-scale batch reactors and full-scale systems, [56][57][58] and it can perform optimization of sludge retention time and nitrogen removal under different DO and return activated sludge flows.…”
Section: Modeling Of Activated Sludge Processesmentioning
confidence: 99%
“…16,35 Real wastewater and sewage sludge are highly heterogeneous with various degradable and inhibitory compounds that result in diverse microbial populations. 43,55 For wellcharacterized populations with known functions, unmeasurable kinetic parameters are predominantly derived from biochemical measurements. 14,16,34,35,40 Although the data-driven component can help correct the estimates and improve the prediction performance, the estimated kinetic parameters do not necessarily reflect the actual activity of those populations.…”
Section: Hybrid Models That Address the Limitations Of Conventional Modeling Strategiesmentioning
confidence: 99%
“…According to Krejny, 2015 [16], wastewater KPIs of Wastewater Treatment Plant [17]. A mathematical model and pilot testing to performing carbon oxidation-nitrification, denitrification and settling was revealed that operational cycles which conducted in the range (120 -400 min), only one (220 min-nitrification: 120 min/ denitrification : 100 min), met fully the nitrogen's effluent criteria and minimum energy consumption [18].…”
Section: Research Frameworkmentioning
confidence: 99%